2015
DOI: 10.1111/1750-3841.12792
|View full text |Cite
|
Sign up to set email alerts
|

Relative Oxidative Stability of Diacylglycerol and Triacylglycerol Oils

Abstract: To compare the oxidative stability between diacylglycerol (DAG) oil and conventional triacylglycerol (TAG) oil (that is, soybean oil), the prepared stripped diacylglycerol oil (SDO) and soybean oil (SSBO) were stored at 60 °C in the dark for 144 h. During storage peroxide values (POVs), contents of aldehydes, unsaturated fatty acids were measured to evaluate the oxidative stabilities of the 2 oils. The results showed the content of C18:2, C18:3, and total unsaturated fatty acid decreased faster in DAG oil than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Qi et al. () have compared the oxidative stability between diacylglycerol oil and soybean oil having a different composition of fatty acids. They have demonstrated that diacylglycerides isolated from diacylglycerol oil of commerce are more vulnerable to an accelerated oxidation compared to triglycerides isolated from soybean oil.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Qi et al. () have compared the oxidative stability between diacylglycerol oil and soybean oil having a different composition of fatty acids. They have demonstrated that diacylglycerides isolated from diacylglycerol oil of commerce are more vulnerable to an accelerated oxidation compared to triglycerides isolated from soybean oil.…”
Section: Assessmentmentioning
confidence: 99%
“…Wang et al (2010) have compared the oxidative stability of a diacylglycerol oil-rich soybean oil with palmolein having a completely different composition of fatty acids and demonstrated that palmolein was more stable. Qi et al (2015) have compared the oxidative stability between diacylglycerol oil and soybean oil having a different composition of fatty acids. They have demonstrated that diacylglycerides isolated from diacylglycerol oil of commerce are more vulnerable to an accelerated oxidation compared to triglycerides isolated from soybean oil.…”
Section: Stability Of the Substance And Reaction And Fate In Foodmentioning
confidence: 99%
“…The DAG content dramatically increased to 16.2% in the crude interesterified oil with a decrement of TAG (60.6%) and MAG (20.9%) content. Most MAG were concentrated in the MD distillate after MD with MAG purity of 82.9%, and DAG and TAG contents in the MD residual rose up to 22.6 and 76.7%, respectively, which revealed a promising applicability in food products due to the fact that DAG‐enriched oils has beneficial health effects though their oxidative stability is controversial depending on their composition and preparation method as well . Kristensen et al found that DAG oil was oxidatively less stable than TAG oil, but the butter blend with DAG oil (40 wt%) was oxidatively more stable than that with TAG oil .…”
Section: Resultsmentioning
confidence: 99%
“…Variations in acylglycerol compositions, as in the case of MAGs and DAGs, may result in changes in oxidative stability. Previous studies have shown contradictory results when comparing the oxidative stability of DAG‐rich oils and traditional TAG oils, since some researchers observed a decreased oxidative stability (Kristensen, Nielsen, Jacobsen, & Mu, ; Qi et al., ; Wang et al., ), whereas others reported a similar or even slightly increased oxidative stability for DAG‐enriched oils (Shimizu, Moriwaki, Nishide, & Nakajima, ). It is not surprising since so many factors can affect the oxidative stability of lipids as have mentioned above.…”
Section: Physicochemical Properties Of Slsmentioning
confidence: 98%
“…Therefore, it is important to keep in mind that other variables should be maintained as the same when investigating the effect of one factor like acylglycerol composition. This has been taken into consideration in the work of Qi et al (2015), where column chromatography was adopted to obtain purified DAGs and TAGs, respectively, so that the difference in their oxidative stability could only result from their different acylglycerol composition and fatty acid composition, which is a forward step to understand the effect of acylglycerol composition on lipid oxidation. Nevertheless, continuous efforts are still required before a definite conclusion can be reached.…”
Section: Acylglycerol Compositionmentioning
confidence: 99%